STRUKTUR DAN FUNGSI CERITA RAKYAT MASYARAKAT MELAYU KECAMATAN SIMPANG HILIR KABUPATEN KAYONG UTARA - Darpid, Darpid; Wartiningsih, Agus; Syahrani, Agus (Universitas Tanjungpura, 2023)
This research aims to find out objectively about the Structure and Function of Malay Folklore of Simpang Hilir District of North Kayong Regency. This research uses a structural approach. The research method used is descriptive with qualitative research forms. The source of this research data is data that comes from speakers. While the data in this study is the folklore